Pengaruh Kompetensi Terhadap Kinerja Pegawai Pada Dinas Pendidikan dan Kebudayaan Kabupaten Ogan Komering Ulu Timur - Nur Jumriatunnisah; Aurantia Marina (Jurnal Cakrawala Akademika, 2024)
The aim of this research is to determine the extent of the influence of competence on employee performance at the East Ogan Komering Ulu Regency Education and Culture Service, with a total sample of 54 people using the saturated sampling method. Meanwhile, for hypothesis testing, a quantitative approach is used by distributing questionnaires with the aim of obtaining data that can be analyzed accurately and the results can be generalized. The results of this research show that competency has a significant effect on employee performance at the East Oku Education and Culture Service.